OPTIMALISASI PARTISIPASI MASYARAKAT DALAM PENINGKATAN MUTU PENDIDIKAN DI SD PLUS AR RAHMAT - Wahyu Hidayat; M. Al Aden Faqih; Ahmad Fawaiz Hakim; Syahrul Fauzi Muharom (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe the forms of community participation, the communication patterns between the school and the community, the impact of community involvement on educational quality, and the challenges encountered in efforts to improve educational quality at SD Plus Ar-Rahmat Cileunyi. The study employed a qualitative descriptive approach. Data were collected through observation, semi-structured interviews, and documentation involving the principal, teachers, parents, school janitor, and security guard selected through purposive sampling. Data were analyzed using the Miles and Huberman model, while data validity was ensured through source and technique triangulation. The findings revealed that community participation was manifested through attendance at school meetings, support for extracurricular activities, contributions to school facilities, and involvement in maintaining school cleanliness and security. Communication between the school and the community was actively conducted through WhatsApp groups, parent meetings, and social media platforms. Such participation positively contributed to increased teacher motivation, the creation of a conducive learning environment, and stronger collaboration between the school and the community. However, several obstacles were identified, including work commitments, limited time, lack of information, distance factors, and low self-confidence among some parents. The study highlights that active and continuous communication plays a crucial role in optimizing community participation to enhance educational quality.